How to protect school children from the neurodevelopmental harms of air pollution by interventions in the school environment in the urban context. (December 2018) - Rivas, Ioar; Querol, Xavier; Wright, John; Sunyer, Jordi
Abstract: Recently, there has been a flurry of publications assessing the effect of air pollution on neurodevelopment. Here we present a summary of the results obtained within the BRain dEvelopment and Air polluTion ultrafine particles in scHool childrEn (BREATHE) Project, which aimed to evaluate the effects of the exposure to traffic related air pollutants in schoolchildren in Barcelona. To this end, we comprehensively characterised air quality in 39 urban schools from Barcelona and identified the main determinants of children's increased exposure. We propose a series of measures to be implemented to improve air quality in schools within the urban context and, consequently, minimise the negative effects on children's neurodevelopment that we found to be associated with the exposure to air pollution. We also aimed to list some of the actions pushed by governments and the society (including school managers, parents, and children) that have been taking place around Europe for promoting better high quality in the school and its surroundings. Highlights: Air pollution was associated with decelerated cognitive development. Traffic should be moved away from schools to improve air quality. Safe school pathways can help promote active travel (e.g.: walk, bicycle). Cleaning should be done after school hours to avoid exposure to ultrafine particles.